2020
DOI: 10.1097/hjh.0000000000002521
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution-associated blood pressure may be modified by diet among children in Guangzhou, China

Abstract: Objectives: To assess the associations between long-term air pollution exposure and blood pressure in children, and to explore the modifying effects of diet on prehypertension and hypertension. Methods: We evaluated 7225 primary school children aged 6–12 years from Guangzhou, China, in 2017. The blood pressure was measured objectively. The individual 1-year average concentration of particles with an aerodynamic diameter of 2.5 μm or less or 10 μm or les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…34 Potential benefits of the plant-based dietary pattern on various health outcomes induced by air pollution were also reported in other contexts. 35,36 Rich antioxidants and anti-inflammatory nutrients from the plant-based dietary pattern may help explain how it could modify the association between long-term PM 2.5 exposure and cognitive function. First, the nutrients like unsaturated fatty acids from vegetable oil were related to lower risks of PM 2.5 associated cardiometabolic diseases, 14,37 through suppressing arrhythmias, modulating autonomic function, and its anti-thrombotic, anti-inflammatory, and vasodilatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Potential benefits of the plant-based dietary pattern on various health outcomes induced by air pollution were also reported in other contexts. 35,36 Rich antioxidants and anti-inflammatory nutrients from the plant-based dietary pattern may help explain how it could modify the association between long-term PM 2.5 exposure and cognitive function. First, the nutrients like unsaturated fatty acids from vegetable oil were related to lower risks of PM 2.5 associated cardiometabolic diseases, 14,37 through suppressing arrhythmias, modulating autonomic function, and its anti-thrombotic, anti-inflammatory, and vasodilatory effects.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Potential benefits of the plant-based dietary pattern on various health outcomes induced by air pollution were also reported in other contexts. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Another study found that long-term exposure to PM 2.5 , SO 2 , and O 3 was associated with increased BP in ≈7000 elementary school children in China. 41 Exposure to a combination of SO 2 , O 3 , NO 2 , and PM 2.5 was also found to be associated with elevated systolic and diastolic BPs. [42][43][44][45][46] Several studies have also reported significant associations between PM 2.5 exposure during childhood and higher BPs or hypertension in adulthood during extended follow-up.…”
Section: Impact On Cardiovascular Risk Factorsmentioning
confidence: 97%
“…Cardiovascular disease is the leading cause of deaths worldwide. It is estimated that 17.8 million people die for it globally in 2017, among which hypertension is the main risk factor for cardiovascular disease and is considered the most important cause of disability and death worldwide (Zhang et al, 2020). A recent study nds that compared with data in 1958 ~ 1959, 1979 ~ 1980, 1991, 2002 and 2012, the crude prevalence rate of hypertension among Chinese residents aged 18 years and above ranges from 18.0 to 44.7% between 2012 to 2015, and the overall prevalence is increasing (Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%